The Reception of the Literary-Aestethic Values of the Qur’an in the Contemporary Literary Criticism in Bosnia and Herzegovina - Babović, Dželila (Prilozi za orijentalnu filologiju, 2017)
The reception of the Qur’an in Bosnia and Herzegovina was for a long time linked to the religious dimension of the Text and its significance in the Islamic culture and civilization. In this matter, the fact that the Qur’an has set up a very intensive contact with the existing literary tradition, by challenging it and finally overcoming it, was neglected. The translations of Enes Karić and Esad Duraković present the first concretization of the Qur’anic text onto the Bosnian language that also attended to the aesthetic pole of the Original, and encourage more encompassing reception of the Qur’an through various models of the analysis of Qur’anic text, which range from stylistic and linguistic prerequisites of texts to its cultural and historical frames. The Qur’anic text has become the subject of the stylistic analysis increasingly often, so its aesthetic and stylistic characteristics have been stressed, as well as the new readings of the Qur’an in the light of the contemporary developments. Thus the relation between the Qur’an and the recipients from Bosnia and Herzegovina has been raised to the diachronic level by achieving the contact and including the Qur’an into the system of contemporary literary values and trends.